Pengembangan Industri Terhadap Kemajuan Teknologi Di Kota Cirebon - Muhammad Yasin; Feriadi Feriadi; Riska Putri Dinarti; Rizky Ramadhani (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
Praise and blessings to God Almighty for His abundant mercy so that we can complete the group assignment that has been given. In this assignment, we have attempted to present the information briefly and concisely, with the aim of providing a general overview of the topics discussed. While this assignment may not be able to explore every aspect in depth, we hope to provide sufficient understanding and answer some questions that may arise. Finally, we would like to thank you, the reader, for your interest and the time you took to read this assignment. Hopefully this assignment can provide new insights and help you understand the topic better. Once again, thank you for this opportunity and hope this assignment meets your expectations.